The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/jpp/rgab163
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnetin: a review of its pharmacology and toxicity

Abstract: Objectives Numerous natural products, including rhamnetin, have been studied in recent years owing to the need for new herbal remedies to treat different illnesses. This study aimed to review the salient properties of rhamnetin and its pharmacological potential and possible toxicological effects. Key findings A search carried out in the ScienceDirect database using the term ‘rhamnetin’ yielded 573 articles published between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Kaempferide is a naturally occurring flavonoid that has been isolated from the roots of Alpinia officinarum [ 98 ]. Like other flavonoids, it has antioxidant properties, anticancer and antihypertensive effects [ 99 , 100 ] and studies have demonstrated that it helps preservation of cardiac function, reduction of oxidative stress, has anti-inflammatory effects, and aids in myocardial infarction size, and cardiomyocyte apoptosis in the case of a reperfusion injury schema [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferide is a naturally occurring flavonoid that has been isolated from the roots of Alpinia officinarum [ 98 ]. Like other flavonoids, it has antioxidant properties, anticancer and antihypertensive effects [ 99 , 100 ] and studies have demonstrated that it helps preservation of cardiac function, reduction of oxidative stress, has anti-inflammatory effects, and aids in myocardial infarction size, and cardiomyocyte apoptosis in the case of a reperfusion injury schema [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin glycosides are also of special interest with respect to human health. For example, rutin is a common component of pharmaceuticals and dietary supplements and isoquercetin can be used as an adjunct therapy agent during cancer treatment. , Other interesting quercetin derivatives are O-methylated conjugates, from which the most common are rhamnetin (7-O-methylquercetin) and isorhamnetin (3′-O-methylquercetin), which also may have a high value of development and application due to their pharmacological activities. , Other O-methylated quercetin conjugates are relatively rare but are also interesting with respect to their potential application, e.g., the presence of 3-O-methylquercetin in the leaves of Nicotiana tabacum L. may be interesting because there is a strong socioeconomic interest in finding an alternative use for tobacco …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Other interesting quercetin derivatives are O-methylated conjugates, from which the most common are rhamnetin (7-O-methylquercetin) and isorhamnetin (3′-O-methylquercetin), which also may have a high value of development and application due to their pharmacological activities. 10,11 Other O-methylated quercetin conjugates are relatively rare but are also interesting with respect to their potential application, e.g., the presence of 3-O-methylquercetin in the leaves of Nicotiana tabacum L. may be interesting because there is a strong socioeconomic interest in finding an alternative use for tobacco. 12 Nucleic acid fragments rich in guanosine have a characteristic spatial structure with important biological properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Natural compounds are generally less toxic than chemical compounds and are readily available in food. Secondary metabolites of plants are valuable resources; in particular, studies on their pharmacological properties are actively pursued [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rhamnetin is a flavonoid derived from Rhamnus petiolaris , Coriandrum sativum , Syzygium aromaticum , and Prunus cerasus [ 25 ] and contains a methoxy group in ring A that provides better metabolic stability and pharmacological effects than non-methoxylated quercetin [ 15 ]. Methylation renders the structure sterically bulky, alters coplanarity, and reduces antioxidant capacity [ 26 ].…”
Section: Introductionmentioning
confidence: 99%